The impact of dose and discontinuation timing of preoperative ACE inhibitors on survival outcomes in cardiac surgery: A MIMIC-IV database analysis - Xiu Zou; Shengyang Chen; Lingyan Hu; Lan Sha; Jianxing Zhou; Hongqiang Qiu; Xuemei Wu (PLoS ONE, 2025)
Background Postoperative mortality following cardiac surgery remains high, highlighting the need to optimize perioperative medication strategies. Angiotensin-converting enzyme inhibitors (ACEIs) exert cardioprotective effects; however, the impact of their preoperative use on postoperative outcomes remains uncertain. This study evaluated the association between preoperative ACEI use and postoperative outcomes in cardiac surgery patients using a large dataset. Methods This retrospective cohort study included patients from the MIMIC-IV database, grouped by preoperative ACEI use and non-ACEI use. Primary outcomes included in-hospital mortality; secondary outcomes included 30-day, 90-day, and 1-year mortality. Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the association between ACEI use and postoperative mortality. Subgroup analyses were used to assess discontinuation timing and lisinopril doses. Propensity score matching was used to control for confounders. Results Of 17,175 patients, 1,516 used ACEIs preoperatively. Cox modeling showed that preoperative ACEI use was significantly associated with reduced in-hospital mortality (HR 0.615; 95% CI 0.506–0.747; p < 0.001) and 30- and 90-day mortality (p < 0.05). Subgroup suggested a significant association between ACEI use and lower mortality in patients without malignancy. Continuing ACEIs on the day of surgery was associated with reduced in-hospital mortality, whereas discontinuation was associated with an attenuation of this beneficial association. A medium lisinopril dose (10–20 mg) was associated with the most consistent reduction in postoperative mortality. Results persisted after propensity score matching (p < 0.001). Conclusions Continuing preoperative ACEI use on the day of surgery was associated with significantly reduced postoperative mortality. Medium-dose lisinopril was associated with the most consistent reduction in postoperative mortality, although patients with malignancy may require individualized assessment. These findings suggest that evidence-based perioperative ACEI management may be beneficial and warrant further investigation.